Outcomes after recto‐anastomosis fistula repair in patients who underwent radical prostatectomy for prostate cancer. (21st November 2013) - Pfalzgraf, Daniel; Isbarn, Hendrik; Reiss, Philip; Meyer‐Moldenhauer, Wolf‐Hartmut; Fisch, Margit; Dahlem, Roland
Abstract : Objectives: To assess fistula recurrence rate and health‐related quality of life (HRQL) after repair, as well as the impact on continence and erection in patients with recto‐anastomotic fistula after radical prostatectomy (RP). In recent publications, the numbers of cases of recto‐urinary fistulae after RP are relatively small. Success rates at fistula closure are good; however, data about functional outcomes and HRQL are more restricted. Patients and Methods: A retrospective study of patients treated for recto‐urethral fistulae after RP between 1993 and 2008. All 17 patients were assessed for fistula recurrence in 2007 and received a standardised non‐validated questionnaire to assess HRQL in 2011; furthermore, a patient's chart review was performed. Surgical technique: fistula closure was abdominal in 10 patients, perineal in five and combined abdominal and perineal in two, some with tissue interposition. Results: In 2007, follow‐up was available for 14 patients, one was deceased and two were lost to follow‐up. The mean follow‐up was 73.3 months and the mean patient age was 63 years. In two of the 17 patients, rectal injury during the initial surgery was reported; another three had undergone adjuvant radiation therapy (18%). In 2011, another two patients were deceased; the mean (range) follow‐up was 99.5 (44–184) months. There was a great improvement in HRQL as compared with before surgery in seven of the 12 evaluable patients, a slight improvement in one and no change in three. In all, eight of the 12 patients were very satisfied with the surgery and four were satisfied. Conclusion: Perineal or abdominal fistula repair yields excellent success rates and high patient satisfaction. However, urinary incontinence can be found in some patients postoperatively, requiring further treatment.